Social Engineering in Building an Integrated Solution Center in Papua to Support the Integrity of the Unitary State of the Republic of Indonesia - Rudiawan, Beni; Amarulla Octavian; Rizerius Eko Hadi Sancoko; Wayan Nuriada; Buddy Suseto; Martinus Dwi Arjanto Widodo; Endah Sri Rejeki (HM Publisher, 2021)
The problem of the High Social Gap in Papua which is the cause of marginalization and discrimination against the Papuan people, as well as the different perceptions of some Indonesians at home and abroad towards armed separatist conflicts are push factors to corner the Indonesian government. In addition, the issue of internationalization of the 1969 referendum mechanism, violations of Human Rights (HAM), and the management of Natural Resources (SDA) by multinational companies that do not have an impact on improving the welfare of the Papuan people also complement the government's opinion of failure. Against the background of these problems, this study uses a quasi-qualitative research method and an exploratory approach with soft systems methodology (SSM) as a data analysis technique to answer the formulation of the problem and research questions. Research data were collected through Focus Group Discussions (FGD), in-depth interviews, and direct discussions with various informants (academics, practitioners, bureaucracy, and community leaders), plus a literature review as secondary data. The results of this study recommend the development of an Integrated Food Estate (IFE) in stages according to customary areas in Papua, which will indirectly support the realization of Territorial Resilience and the Universal Defense System (Sishta). Furthermore, to ensure that all these processes are carried out properly and continuously, this study recommends the establishment of an Integrated Solution Center (ISC). With the implementation of these recommendations, it is hoped that the peaceful and prosperous Papuan people will soon be realized.